• Accueil
• Math
• Exercise: find (fog) and (gof).given f(x) = 3x +...

# Exercise: find (fog) and (gof).given f(x) = 3x + 1 and g(x) = x+ 7​

• Réponse publiée par: nelspas422

fog= 3x+1

=3(x+7)+1

=3×+21+1

=3×+1

goh=x+7

=3x+1+7

=3x+8

• Réponse publiée par: cleik

(f+g)(x)=x²+3x-1

Step-by-step explanation:

f(x)=3x+1

g(x)=x²-2

(f+g)(x)= 3x+1+x²-2

(f+g)(x)=x²+3x-1

• Réponse publiée par: homersoncanceranguiu

1. (f o g)(x) = 3x+22

(g o f)(x) = 3x+8

2. (f o g)(x) = 3x+3

(g o f)(x) = 3x+1

Step-by-step explanation:

1. (f o g)(x) = f(g(x))

= f(x+7)

= 3(x+7)+1

= 3x+21+1

= 3x+22

(g o f)(x) = g(f(x))

= g(3x+1)

= 1(3x+1)+7

= 3x+1+7

= 3x+8

2. (f o g)(x) = f(g(x))

= f(3x+4)

= 1(3x+4)-1

= 3x+4-1

= 3x+3

(g o f)(x) = g(f(x))

= g(x-1)

= 3(x-1)+4

= 3x-3+4

= 3x+1

• Réponse publiée par: taekookislifeu

1.)

(f o g) (x) = f(g(x))

= x+7

= 3(x+7)+1

= 3x+21+1

=3x+22

(g o f) (x) = g(f(x))

= 3x+1

=3x+1+7

= 3x+8

2.)

(f o g) (x) = f(g(x))

= 3x+4

=3x+4-1

= 3x+3

(g o f) (x) = g(f(x))

= x-1

= 3(x-1)+4

= 3x-3+4

3x+1

• Réponse publiée par: nelspas422

1.f^-1(x)=x-1/3

2. g^-1(x)=x+2

3. it has no inverse function

4. f^-1(x)=x-7/2

• Réponse publiée par: 09389706948

• Réponse publiée par: reyquicoy4321

D)  3x^3 +x^2 -18x -6

Step-by-step explanation:

The distributive property applies.

(f·g)(x) = f(x)·g(x) = (3x +1)(x^2 -6) = 3x(x^2 -6) +1(x^2 -6)

(f·g)(x) = 3x^3 -18x +x^2 -6 . . . . . eliminate parentheses

(f·g)(x) = 3x^3 +x^2 -18x -6 . . . . put in standard form

• Réponse publiée par: aimeedelacruz24

4×+1

Step-by-step explanation:

3×-1+(×+2)

3×-1+×+2

3×+×-1+2→combine like terms

=4×+1

• Réponse publiée par: hannahleigh